Audio-Visual Media to Enhance Learning Motivation in Indonesian Language Subject for the 3rd-Grade of Islamic Elementary School - Rohmah, Fina Zainur; Yunianta, Rohmat Dwi; Ichsan, Ahmad Shofiyuddin (Ibtida'i, 2024)
One significant reason for the low motivation among students is the lack of creative media in the learning process. This study aims to investigate the effectiveness of audio-visual media in enhancing learning motivation in the Indonesian language subject for Grade III at Madrasah Ibtidaiyah. This field research, conducted at Madrasah Ibtidaiyah Al-Ma’had An Nur Bantul, employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing or verification, with source triangulation ensuring data validity. The study's findings include the implementation of contextual teaching methods, delivery of Indonesian language material using concrete objects aided by audio-visual media, and positive student responses to these methods. The application of contextual teaching in the Indonesian language subject for Grade III led to students discovering the meaning of learning through direct experiences, becoming more active in learning, and showing significant development in literacy skills. This study underscores the importance of incorporating creative media, particularly audio-visual aids, to enhance student motivation and engagement in the learning process